2. Consider the following functions: p(x) = x² - 2x + 1 q(x) = 2x+1 X-1 r(x)=x²-x² + 3x + 1 s(x) = x² + 3x + 5 t(x) = 2x + 1 u(x)=2x-1 v(x) = x³ - 2x - 1 a. Express f₁(x) = x² +2 as a sum or difference of any two given functions. b. Express f₂(x)= x³ as a sum or difference of any two given functions. c. Express f₁(x) = -x² + 4x as a sum or difference of any two given functions. d. Express f(x) = -5x-4 as a sum or difference of any two given functions. e. Express f(x)=x²-x²-5x-6 as a sum or difference of any two given functions.